Cybersecurity - Michael Veale; Ian Brown (Internet Policy Review, 2020)
Cybersecurity covers the broad range of technical and social issues that must be considered to protect networked information systems. The importance of the concept has increased as so many government, business, and day-to-day activities globally have moved online. It has been increasingly referred to in both academic and mainstream publications since 2003, in fields including software engineering, international relations, crisis management and public safety, slowly overtaking more technical terms such as computer/system/data security (popular in the 1970s/1980s) and information security (popular from the mid 1990s). But its strong association with national security and defence agencies, and disconnection from social science notions such as place, have led to concerns of inappropriate cyber securitisation of government programmes.
Keywords: 300; Cyber; Governance; Hacking; Securitisation; Surveillance